Social stress induces neurovascular pathology promoting depression - Menard, Caroline; Pfau, Madeline L.; Hodes, Georgia E.; Kana, Veronika; Wang, Victoria X.; Bouchard, Sylvain; Takahashi, Aki; Flanigan, Meghan E.; Aleyasin, Hossein; LeClair, Katherine B.; Janssen, William G.; Labonté, Benoit; et al. (Nature neuroscience, 2017)
Studies suggest that heightened peripheral inflammation contributes to the pathogenesis of major depressive disorder. We investigated the effect of chronic social defeat stress, a mouse model of depression, on blood–brain barrier (BBB) permeability and infiltration of peripheral immune signals. We found reduced expression of the endothelial cell tight junction protein claudin-5 (Cldn5) and abnormal blood vessel morphology in nucleus accumbens (NAc) of stress-susceptible but not resilient mice. CLDN5 expression was also decreased in NAc of depressed patients. Cldn5 downregulation was sufficient to induce depression-like behaviors following subthreshold social stress whereas chronic antidepressant treatment rescued Cldn5 loss and promoted resilience. Reduced BBB integrity in NAc of stress-susceptible or mice injected with adeno-associated virus expressing shRNA against Cldn5 caused infiltration of the peripheral cytokine interleukin-6 (IL-6) into brain parenchyma and subsequent expression of depression-like behaviors. These findings suggest that chronic social stress alters BBB integrity through loss of tight junction protein Cldn5, promoting peripheral IL-6 passage across the BBB and depression. Chronic social defeat stress induces loss of protein claudin-5, leading to abnormalities in blood vessel morphology, increased blood brain barrier permeability, infiltration of immune signals and depression-like behaviors.